Interhemispheric insular and inferior frontal connectivity are associated with substance abuse in a psychiatric population. (May 2015) - Viswanath, Humsini; Velasquez, Kenia M.; Savjani, Ricky; Molfese, David L.; Curtis, Kaylah; Molfese, Peter J.; Eagleman, David M.; Baldwin, Philip R.; Frueh, B. Christopher; Fowler, J. Christopher; Salas, Ramiro
Abstract: Substance abuse is highly comorbid with major psychiatric disorders. While the neural underpinnings of drug abuse have been studied extensively, most existing studies compare drug users without comorbidities and healthy, non-user controls. Such studies do not generalize well to typical patients with substance abuse disorders. Therefore, we studied a population of psychiatric inpatients (n = 151) with a range of mental illnesses. Psychiatric disorders were diagnosed via structured interviews. Sixty-five percent of patients met criteria for at least one substance use disorder. Patients were recruited for resting state functional connectivity (RSFC) and diffusion tensor imaging (DTI) experiments to examine the interhemispheric connectivity between brain regions hypothesized to be involved in drug addiction, namely: the inferior, medial, and superior frontal gyri; insula; striatum; and anterior cingulate cortex. The World Health Organization Alcohol, Smoking, and Substance Involvement Screening Test (WHOA) questionnaire was used to further assess drug use. An association between use of tobacco, alcohol, cocaine, sedatives, and hallucinogens with increased insular interhemispheric connectivity was observed. In addition, increased inferior frontal gyrus interhemispheric connectivity was associated with amphetamine and inhalant use. Our results suggest that increased inter-hemispheric insula connectivity is associated with the use of several drugs of abuse. Importantly, psychiatric inpatients without a history of drug dependence were used as an ecologically valid control group rather than the more typical comparison between "mentally ill vs. healthy control" populations. We suggest that dysfunction of interhemispheric connectivity of the insula and to a lesser extent of the inferior frontal gyrus, are related to drug abuse in psychiatric populations. Highlights: We studied MRI resting state functional connectivity in psychiatric patients. We correlated substance use disorders to interhemispheric connectivity. Insular and frontal gyral connectivity correlated with abuse of specific drugs.